Vitreous lavage fluid and bronchoalveolar lavage fluid have equal diagnostic value in sarcoidosis. Issue 49 (December 2016) - Maruyama, Kazuichi; Inaba, Tohru; Tamada, Tsutomu; Nakazawa, Toru
Abstract : Abstract: Here, we elucidate the immunological features of both bronchoalveolar lavage fluid (BALF) and vitreous lavage fluid (VLF) samples from patients with histopathologically verified sarcoidosis. In addition, we assess the safety of vitrectomy in sarcoidosis patients by investigating the occurrence of complications and the recovery of visual acuity. Twenty-two eyes of 22 patients with tissue-proven sarcoidosis were enrolled in this study. BALF and VLF samples were obtained and compared in each patient, and the clinical course (including visual acuity) was followed. The presence of sarcoidosis was assessed with a flow cytometric analysis of T-lymphocytes in the BALF and VLF samples. Our results indicated that the CD4 T-cell population and the CD4/CD8 ratio were significantly higher in the VLF T-lymphocytes than the BALF T-lymphocytes. On the other hand, the CD8+ T-cell population was significantly lower in the VLF T-lymphocytes. Therefore, our findings suggest that VLF samples have a high diagnostic value (equal to that of BALF samples) for sarcoidosis. Moreover, we found that the sample collection did not affect visual acuity and that there were no adverse events after surgery. A flow cytometric analysis of a VLF sample may therefore be a useful adjunct in the diagnosis of sarcoidosis.